PCOS-GWAS Susceptibility Variants in THADA, INSR, TOX3, and DENND1A Are Associated With Metabolic Syndrome or Insulin Resistance in Women With PCOS - Tian, Ye; Li, Jingyu; Su, Shizhen; Cao, Yongzhi; Wang, Zhao; Zhao, Shigang; Zhao, Han (Frontiers in Endocrinology, 2020)
Polycystic ovary syndrome is characterized by reproductive and metabolic disturbances throughout the female lifespan. Therefore, this study aimed to determine whether genome-wide association studies (GWAS)-identified risk variants for PCOS could confer risk of metabolic syndrome (MS) or insulin resistance (IR). Fifteen independent SNPs mapping to 11 GWAS loci genotyped in a total of 2082 Han Chinese women independent of previous GWAS and phenotype-genotype correlations were assessed. The CC group for rs12478601 in THADA was associated with decreased rate of MS after adjustment for age (23.2% vs 27%, P = 0.042, OR = 0.81). Using a dominant model, the GG+AG group for rs2059807 in INSR was associated with increased risk of MS after adjustment for age (26.8% vs 22.5%, P = 0.023, OR = 1.27). The GG + GT group for rs4784165 in TOX3 was found to be associated with an increased rate of IR after adjustment for age and BMI(53.3% vs 48.5%, P = 0.027, OR = 1.27).The GG+AG group for rs2479106 in DENND1A was associated with a decreased rate of IR (48.3% vs 53.6%, adjusted P = 0.039, OR = 0.80). After exclusion of PCOS cases with a family history of diabetes, hypertension, or dyslipidemia, the phenotype-genotype correlations between the genes INSR and TOX3 and MS or IR were still significant (P < 0.05). Three SNPs (rs13429458 in THADA, rs10818854 in DENND1A, and rs2059807 in INSR) were significantly associated with IR; however, their association was not significant after adjustment for age and BMI. This genotype-phenotype study thus provides clues that THADA, INSR, TOX3, and DENND1A play a role in PCOS possibly through a metabolic disorder-related pathway.